Improved Nitrogen Use Efficiency and Greenhouse Gas Emissions in Agricultural Soils as Producers of Biological Nitrification Inhibitors - Shah Saud; Depeng Wang; Shah Fahad (Frontiers in Plant Science, 2022)
Based on an analysis of the current situation of nitrogen fertiliser application, it is suggested that improving the nitrogen utilisation efficiency of crops is an important means of promoting the sustainable development of agriculture and realises the zero increase in chemical fertiliser application. Nitrate loss and nitrous oxide (N2O) emissions caused by nitrification and denitrification are the main reasons for the low utilisation rate of nitrogen fertilisers. N2O is a greenhouse gas that has caused a sharp increase in global temperature. Biological nitrification inhibition refers to releasing natural compounds that inhibit nitrification from plant roots. The natural compounds released are called biological nitrification inhibitors (BNIs), which specifically inhibit the activity of microorganisms in soil nitrification. Biological nitrification inhibitors can significantly improve rice (Oryza sativa), corn (Zea mays) and other crops by 5–10%, which can increase the nitrogen utilisation rate of corn by 3.1%, and reduce greenhouse gas N2O emissions. Compared with plants that do not produce BNI, the amount of N2O released can be reduced by up to 90%. The BNI released by Brachialactone (Brachiaria humidicola) accounted for 60–90% of the total inhibition of nitrification. In summary, biological nitrification inhibitors that inhibit nitrification, improve nitrogen utilisation and crop yield, and reduce greenhouse gas emissions play an important role. This paper reviews the plants known to release BNIs, reviews the plants known to inhibit soil nitrification but with unknown BNIs and further discusses the important role of bio nitrification inhibition in agricultural systems.